The implications of illicit networks for changes in anti-narcotics policies - Arias, Enrique Desmond (Crime, law and social change, 2024)
Mexico, like many other countries in Latin America and the Caribbean suffering persistent violence, has sought to shift its anti-narcotics and organized crime control policies to develop more effective responses to the crime challenges that the country faces. Building on research in Brazil, Colombia, Jamaica, and Mexico, this essay develops an analysis of crime as embedded within political, social, and economic networks that provide criminal activity with broad cross-sectoral support. This cross-sectoral support for criminal activity - which can involve both official corruption but also social support from entrepreneurs and popular sectors - helps to sustain crime even in the face of evolving state policy. We argue that different forms of crime control policy are affected in different ways by these illicit networks. The essay identifies three forms of policy - market suppression, organizational suppression, and behavioral modification - and examines through case studies the implications of internal and external illicit networks for these policies. López Obrador distanced his administration from the militarized security policy of the previous administrations, and yet has merely rebranded many of these existing policies. Without a policy that specifically addresses these illicit networks, any more novel interventions risk repeating the mistakes of the past.